Clinical, dermoscopic, and ultrasonic monitoring of the response to biologic treatment in patients with moderate-to-severe plaque psoriasis - Wang, Juncheng; Zhu, Qingli; Li, Feng; Xiao, Mengsu; Liu, Jie (Frontiers in Medicine, 2023)
Background: Assessment of therapeutic response of psoriasis has relied traditionally on clinical observation and effective non-invasive tools are desirable. Objectives: To investigate the value of dermoscopy and high-frequency ultrasound (HFUS) in monitoring of psoriatic lesions treated with biologics. Methods: Patients with moderate to severe plaque psoriasis treated with biologics were evaluated by clinical, dermoscopic and ultrasonic scores at weeks 0, 4, 8 and 12. Clinical scores, including Psoriasis Area Severity Index (PASI) and target lesion score (TLS), were evaluated at representative lesions. Dermoscopy was performed to assess the red background, vessels and scales on a 4-point scale and the presence of hyperpigmentation, hemorrhagic spots and linear vessels. HFUS was performed to measure thicknesses of superficial hyperechoic band and subepidermal hypoechoic band (SLEB). The correlation between clinical, dermoscopic and ultrasonic evaluation were also analyzed. Results: 24 patients were analyzed and achieved 85.3% and 87.5% reduction of PASI and TLS, respectively, after 12 weeks of treatment. The red background, vessels, scales scores under dermoscopy were reduced by 78.5%, 84.1% and 86.5%, respectively. Some patients developed hyperpigmentation and linear vessels after treatment. Hemorrhagic dots slowly subside over therapeutic course. Ultrasonic scores were significantly improved with average reduction of 53.9% in superficial hyperechoic band thickness and 89.9% in SLEB thickness. TLS in the clinical variables, scales in dermoscopic variables, and SLEB in ultrasonic variables decreased the most significantly in the early stage of treatment (week 4) with 55.4%, 57.7%, and 59.1% (P > 0.05), respectively. Most of the variables, including the red background, vessels, scales and SLEB thickness, were strongly correlated with TLS. The high correlations were also found between the SLEB thickness and the red background or vessels scores, and between the superficial hyperechoic band thickness and the scales scores. Conclusions: Both dermoscopy and HFUS were useful in therapeutic monitoring of moderate to severe plaque psoriasis.